Dynamic 1H‐MRS for detection of 13C‐labeled glucose metabolism in the human brain at 3T. Issue 3 (31st January 2020) - Dehghani, Masoumeh; Zhang, Steven; Kumaragamage, Chathura; Rosa‐Neto, Pedro; Near, Jamie
Abstract : Purpose: In 2004, Boumezbeur et al proposed a simple yet powerful approach to detect the metabolism of 13 C‐enriched substrates in the brain. Their approach consisted of dynamic 1 H‐MRS, without a 13 C radiofrequency (RF) channel, and its successful application was demonstrated in monkeys. Since then, this promising method has yet to be applied rigorously in humans. In this study, we revisit the use of dynamic 1 H‐MRS to measure the metabolism of 13 C‐enriched substrates and demonstrate its application in the human brain. Methods: In healthy participants, 1 H‐MRS data were acquired dynamically before and following a bolus infusion of [1‐ 13 C] glucose. Data were acquired on a 3T clinical MRI scanner using a short‐TE SPECIAL sequence, with regions of interest in both anterior and posterior cingulate cortex. Using simulated basis spectra to model signal changes in both 12 C‐bonded and 13 C‐coupled resonances, the acquired spectra were fit in LCModel to obtain labeling time courses for glutmate and glutamine at both C4 and C3 positions. Results: Presence of the 13 C label was clearly detectable, owing to the pronounced effect of heteronuclear ( 13 C‐ 1 H) scalar coupling on the observed 1 H spectra. A decrease in signal from 12 C‐bonded protons and an increase in signal from 13 C‐coupled protons were observed. The fractional enrichment of Glu‐C4, (Glu+Gln)‐C4, and (Glu+Gln)‐C3 at 30 minutes following infusion of [1‐ 13 C] glucose was similar in both regions: 11% to 13%, 9% to 12% and 3% to 5%, respectively. Conclusion: These preliminary results confirm the feasibility of the use of dynamic 1 H‐MRS to monitor 13 C labeling in the human brain, without a 13 C RF channel.